Leadership and job satisfaction among physicians in the Cyprus public healthcare system - Gregoriou, Ioanna; Economidou, Eleftheria C.; Avraam, Demetris; Soteriades, Elpidoforos S.; Papastavrou, Evridiki; Charalambous, Andreas; Stylianides, Antonis; Merkouris, Anastasios (Springer Science and Business Media LLC, 2026)
Introduction
Leadership and job satisfaction constitute important characteristics of health professionals’ employment status. We evaluated the association between physicians’ leadership and job satisfaction among health professionals in the public health sector of Cyprus.
Methods
A cross-sectional survey with self-administered questionnaires was implemented among all physicians from the public health sector of Cyprus (Ministry of Health, administration offices, public hospitals and healthcare centers). In this context we used two standardized internationally validated instruments: the Multifactor Leadership Questionnaire (MLQ-5X), and the Job Satisfaction Survey (JSS).
Results
A total of 690 eligible physicians were invited to participate, of whom 511 completed the survey and 9 were excluded. A final sample of 502 physicians (262 male and 235 female) were included in the statistical analyses. The mean participants’ age was 47.7 years (SD = 9.2), whilst the mean number of years of experience in the public sector was 12.4 years (SD = 8.4). Transactional and transformational leadership were strongly associated with six out of the nine job satisfaction subscales, as well as with the total job satisfaction scale. Passive leadership was negatively associated with job satisfaction. Overall, total leadership showed a strong statistically significant association with total job satisfaction [odds ratio = 3.88, 95% CI (2.27, 6.63)].
Conclusion
We found strong and statistically significant associations between transactional and transformational leadership styles and health professionals’ job satisfaction in most of the job satisfaction subscales. Establishing a causal relationship between the above requires further investigations with appropriate study design.